A Review on Energy Efficient Load Balancing Algorithm Using Cloud Computing (International Journal of Food and Nutritional Sciences, 2022)
As it provides utility-oriented services based on a pay-as-you-go model over the network, cloud computing is now the most developing area. Large organisations are moving their workloads to the cloud as a result of the availability of scalable on-demand resources and the supply of services globally. The amount of energy consumed by the data centres that host these cloud computing applications has significantly increased due to the growing demand for cloud services and high data centre usage. High operational costs and environmentally unfavourable carbon footprint emissions are caused by data centres' high energy usage. In order to minimise the high operational cost and also to decrease CO2 dissipation, we must emphasise and research numerous green cloud computing solutions. In order to decrease energy usage, this study explores a variety of energy-efficient strategies. Additionally, comparative research is done to recommend improved future initiatives.